Abstract 13342: Validation of the European Society of Cardiology Systematic Coronary Risk Evaluation 2 Prediction Algorithms in a Non-European (United States) Contemporary, Community-Based Historical Cohort - Medina-Inojosa, Betsy J; Medina-Inojosa, Jose R; Sheffeh, Mohammad Ali; Bianchettin, Rosana; Lerman, Amir; Lopez-Jimenez, Francisco (Circulation (New York, N.Y.), 2022)
IntroductionNewly developed Systematic Coronary Risk Evaluation-2 (SCORE-2) and the version for older people [(SCORE2-OP) ≥70 years] algorithms for 10-yr incident cardiovascular disease (CVD) have been derived incorporating European and US populations. Its performance has not been externally validated in community-based populations representative of real-world clinical practice. HypothesisWe tested the hypothesis that the SCORE-2 and SCORE2-OP algorithms will accurately estimate 10-yr risk of first-onset CVD in this population. MethodsConsecutive patients who, between 1998-2000, sought primary care in Olmsted county, MN, and were followed-up using the Rochester Epidemiology Project. Inclusion criteria were set as those used in the derivation of the original algorithm. The composite outcome of CVD was defined as first myocardial infarction, ischemic stroke, or cardiovascular mortality. We compared predicted and observed events and generated C-statistics across predefined risk subgroups. ResultsWe included 22,858 adults, mean age of 55.11±11.58 (13.50% >70 yr) 54% females. After a mean follow-up of 9.55±1.5 yr, 2,145 events were observed. 6.39% of subjects for SCORE-2 and 59.88% using SCORE2-OP were considered at high risk. Overall, the SCORE-2 had better discrimination than the SCORE2-OP (C-statistic0.72 and 0.64, respectively) (Fig B-D). The algorithms performed better in individuals 50-69 yr while underpredicting in younger individuals and overpredicting CVD in ages above 70 (in the low and moderate risk group) (Fig A-C). Prediction was mostly similar between men, women and middle-aged individuals but demonstrated pronounced underprediction in older men (Fig B-D). ConclusionsThe SCORE-2 Risk prediction tool performed with marginal results whereas the SCORE2-OP had poor performance when predicting CVD events in a community cohort representing real-world clinical practice in a non-European population.